"You Know, I Swipe My Card and Hope for the Best": Technology and Cognition as Dual Landscapes of Change. (October 2022) - Heatwole Shank, Kendra S.
Mild cognitive impairment (MCI), or objective and subjective cognitive decline, affects an estimated 15%–20% of individuals over the age of 65 . People with MCI generally live in community settings but may be at risk for functional changes in out-of-home participation, particularly when their instrumental activities are cognitively demanding or complex. Technology is part of the interface in complex person-place relationships. The purpose of this study is to examine the nature of everyday technology use in the context of out-of-home participation for community-dwelling older adults with MCI. Community-dwelling older adults with MCI (MoCA <26, >17; ( n  = 10)) were recruited for data collection using a Go-along method (naturalistic observation, semi-structured interviews, and photography) for multiple out-of-home activities. Findings from this project suggested that participants felt that technology, like their cognition, was out of their control and difficult to predict or change. Four ways the participants experienced the "technology landscape" in their daily lives included: enabling being present, facilitating participation, impeding goals, and constricting options. We present a model of the intersection of cognition, participation, and technology in daily life, and discuss ways that technology can most effectively be used to extend well-being for a population aging in place.